Linguopragmatic features of the Discourse Markers - Dossanova, А.М.; Maral, А.М.; Sharshova, Р.Н. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2025)
This article analyzes the linguopragmatic features of discourse markers based on the material of modern Kazakh-language podcasts. The relevance of the research is due to the rapid development of podcasts in Kazakh language, which reflect new trends in modern oral speech. The paper reveals the functions of discourse markers, including their role in the organization of speech, the formation of interaction between speaker and listener, as well as in the transmission of modality and emotional coloring of utterance. The research used methods of contextual and structural analysis, continuous sampling and observation. Transcribed audio recordings of podcasts were used as the main material. Discourse markers are classified as regulatory and organizing, and their pragmatic functions in media discourse are considered comprehensively. The results of the study show that discourse markers play an important role in ensuring the coherence of the text and effective communication in oral speech. The practical significance of the work lies in the possibility of using the data obtained to develop communication skills, improve linguopragmatic competence and analyze media texts. This study reveals the features of the functioning and classification of discourse markers in Kazakh language and can serve as a basis for further applied and theoretical research.